2003
DOI: 10.1111/j.1572-0241.2003.07419.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantitative Analysis of Nocturnal Jejunal Motor Activity Identifies Abnormalities in Individuals and Subgroups of Patients With Slow Transit Constipation

Abstract: Thirty-seven patients with STC underwent 24-h ambulatory jejunal manometry; data were compared with those obtained in 38 healthy controls. Automated quantitative analysis of seven variables of the nocturnal migrating motor complex was performed, to assess whether differences existed between groups, and whether individual patients had evidence of small intestinal dysmotility, defined as two or more measures of migrating motor complex variables outside the normal range. Four variables differed significantly betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 68 publications
0
30
2
2
Order By: Relevance
“…Recording System and Study Protocol Study methodology has been described in detail elsewhere [10,23]. In brief, duodeno-jejunal motility was monitored via three miniature strain gauge transducers mounted on a soft, nasojejunal catheter (Gaeltec, Dunvegan, Isle of Skye, Scotland/Unisensor AG, Attikon, Switzerland; outer diameter 2.5 mm, length 2.5 m).…”
Section: Prolonged Ambulatory Small Bowel Manometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Recording System and Study Protocol Study methodology has been described in detail elsewhere [10,23]. In brief, duodeno-jejunal motility was monitored via three miniature strain gauge transducers mounted on a soft, nasojejunal catheter (Gaeltec, Dunvegan, Isle of Skye, Scotland/Unisensor AG, Attikon, Switzerland; outer diameter 2.5 mm, length 2.5 m).…”
Section: Prolonged Ambulatory Small Bowel Manometrymentioning
confidence: 99%
“…Initially, patients with constipation can be classified simply on the basis of colonic transit and rectal evacuatory function [3,4]. In a subset of patients with a proven delay in colonic transit (slow transit constipation, STC), however, gut dysfunction may extend beyond the colorectum, and several reports have described co-existent upper gastrointestinal (GI) tract motor abnormalities involving the esophagus, stomach, gallbladder, and small intestine [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, such studies have shown that approximately half of constipated patients will have delayed colonic transit (range 13-80%) (17,38). Furthermore, a proportion of these patients have upper gastrointestinal (GI) symptoms, and evidence of a panenteric motor disorder may be found in 18 -72% (42,47). This is of clinical significance, as such patients may have poorer outcome to intervention compared with those patients with an isolated colonic disorder (40).…”
mentioning
confidence: 99%
“…Small intestinal manometry has now been undertaken in over fifty patients with severe midgut dysmotility, and the abnormalities seen in the patients all conform to this description. What is striking about the findings is that they are the characteristic manometric abnormalities described in patients with chronic idiopathic intestinal pseudo-obstruction (CIIP; Stanghellini et al 1987); findings, in turn, that are generally considered predictive of enteric neuropathy as the dominant lesion (Stanghellini et al 1987;Quigley et al 1997;Camilleri et al 1998;Wingate et al 2002;Scott et al 2003).…”
Section: Severe Midgut Dysmotilitymentioning
confidence: 99%